Adult learning theories and autoethnography: Informing the practice of information literacy. (June 2020) - Bordonaro, Karen
The learning theories of self-directed learning and lifelong learning can inform the practice of information literacy in higher education for adult learners. These theories lend themselves to the use of autoethnography, a research methodology that relies on the exploration of lived experiences through reflexivity informed by theory. In conducting an autoethnography on information literacy, its practice appears as both a singular and a collective activity. Multiple ramifications for practice come from this exploration. These ramifications include considerations of choices, barriers, conducive learning environments, informal learning opportunities, and the need for reflection for adult learners. Applying the learning theories of self-directed learning and lifelong learning to the practice of information literacy offers librarians new and useful perspectives on its practice with adult learners.